2016
DOI: 10.1111/sltb.12237
|View full text |Cite
|
Sign up to set email alerts
|

Lifetime and 12‐Month Nonsuicidal Self‐Injury and Academic Performance in College Freshmen

Abstract: We examined whether nonsuicidal self‐injury (NSSI) is associated with academic performance in college freshmen, using census‐based web surveys (N = 7,527; response = 65.4%). NSSI was assessed with items from the Self‐Injurious Thoughts and Behaviors Interview and subsequently linked with the administratively recorded academic year percentage (AYP). Freshmen with lifetime and 12‐month NSSI showed a reduction in AYP of 3.4% and 5.9%, respectively. The college environment was found to moderate the effect of 12‐mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
67
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 83 publications
(76 citation statements)
references
References 70 publications
4
67
1
4
Order By: Relevance
“…Between 2014 and 2016, all 8,530 freshmen were eligible for inclusion in the study (i.e., census sampling ). Detailed recruitment strategies of the LCS are described elsewhere (Kiekens et al., ). In brief, all eligible students were invited to participate, with nonrespondents sent up to seven reminder emails.…”
Section: Methodsmentioning
confidence: 99%
“…Between 2014 and 2016, all 8,530 freshmen were eligible for inclusion in the study (i.e., census sampling ). Detailed recruitment strategies of the LCS are described elsewhere (Kiekens et al., ). In brief, all eligible students were invited to participate, with nonrespondents sent up to seven reminder emails.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, this is the first study that investigates the association between BPB and objective academic performance, and so our approach is exploratory in nature. As previous studies found that certain sociodemographic characteristics and mental health problems were related to reduced academic performance (Auerbach et al, ; Bruffaerts et al, ; Kiekens et al, ; Mortier et al, ), we controlled for sociodemographic confounders and the presence of other mental health problems.…”
Section: Introductionmentioning
confidence: 99%
“…Predictors included in this study are well-established risk factors for STB (Nock et al, 2012) that have also shown to be related to college STB: parental psychopathology (Abramson et al, 1998; Wilcox et al, 2010), early traumatic experiences (Gibb et al, 2001; Zhang and Tao, 2013), mental disorders (Paul et al, 2015; Whitlock et al, 2013), and recent stressful experiences (Chou et al, 2013; You et al, 2014). We build on earlier LCS studies that found self-injurious behaviours to be widespread among incoming freshmen (Kiekens et al, 2016; Mortier et al, 2015). The current study’s objectives are to: (1) estimate one-year incidence proportions of first-onset STB during college, (2) evaluate individual-level and population-level risk for first-onset STB, and (3) test a multivariate model for first-onset STB in terms of prediction accuracy.…”
Section: Introductionmentioning
confidence: 99%